The Evaluation of Image Messages in MP3 Audio Steganography Using Modified Low-Bit Encoding - Ilham Firman Ashari (Telematika, 2021)
Information security is an important aspect of maintaining the confidentiality of information. One type of document kept secret is images (.jpg, .png, .gif, dan .bmp). MP3 audio files are popular audio files that can be used as a medium for steganography. The method implemented in this study uses Base64 in the image and the insertion method used is using Low-Bit Encoding (LBE). In this study, the parameters of the value of LBE will be evaluated. The purpose of the evaluation is to compare the LBE parameter parameters that are the most optimal in securing the message while taking into account the quality of steganographic files. The results obtained from the study are the proposed method that supports the imperceptibility aspect seen from the image histogram and audio frequency spectrum. The fidelity aspect is seen from the PSNR and SNR values, where The optimal value on the LBE + 2 parameter is by considering the capacity of the picture message that can be inserted and audio quality. PSNR LBE + 2 values range from 50-60 dB with SNR different about 0.01% from LBE + 1. The proposed method does not support the robustness aspect because it is not resistant to attacks by bit rate manipulation and channel mode. The test results on the recovery aspect are worth 100%, meaning that the image's quality and size before and after extraction will be the same. And finally, the test results on the payload aspect, there is an increase in message capacity with LBE + 2 around 12.5% of LBE + 1, and using LBE + 3 will increase the maximum size around 25% of LBE + 1 and about 14% of LBE + 2. The insertion and extraction time for LBE + 3 is slower compared to the others.